Advanced materials modelling for structures - Kruch, Serge; Altenbach, Holm (Advanced Structured Materials, 2013)
This volume presents the major outcome of the IUTAM symposium on "Advanced Materials Modeling for Structures". It discusses advances in high temperature materials research, and also to provides a discussion  the new horizon of this fundamental field of applied mechanics. The topics cover a large domain of research but place a particular emphasis on multiscale approaches at several lengthscales applied to non linear and heterogeneous materials. Discussions of new approaches are emphasised from various related disciplines, including metal physics, micromechanics, mathematical and computational mechanics.